Bergapten Improves Scopolamine-Induced Memory Impairment in Mice via Cholinergic and Antioxidative Mechanisms - Kowalczyk, Joanna; Kurach, Łukasz; Boguszewska-Czubara, Anna; Skalicka-Woźniak, Krystyna; Kruk-Słomka, Marta; Kurzepa, Jacek; Wydrzynska-Kuźma, Małgorzata; Biała, Grażyna; Skiba, Adrianna; Budzyńska, Barbara (Frontiers in Neuroscience, 2020)
Bergapten is a furanocoumarin naturally-occurring in the Apiaceae family and it is a well-known photosensitizing agent used in photochemotherapy. In this study we investigated the protective effect of bergapten and its underlying mechanism of action against scopolamine-induced memory impairment in male Swiss mice. The passive avoidance test was used to evaluate efficiency of memory acquisition and consolidation. The results demonstrated that both single and repeated administration of bergapten improved not only the acquisition, but also consolidation of memory. The behavioral tests showed that bergapten prevented memory impairment induced by injection of scopolamine. Observed effects could be due to the inhibition of acetylcholinesterase activity in the hippocampus and prefrontal cortex. Also, bergapten caused significant anti-oxidative effect. These new findings provide pharmacological and biochemical support for the development of the coumarin’s potential in cognitive deficits.